Integrated pest management for German cockroach (Blattella germanica L.) in selected urban communities in Yasuj, Iran - Shahraki, Gholam Hossein (2011)
A study was conducted to assess the effectiveness of IPM approach as well as cost effective comparison of IPM and conventional control approaches against the German cockroach infestation in selected urban communities in South Western Iran. The purpose of the study was to determine the efficacy of sanitation on infestation in the residential buildings. In addition, the distribution and dispersion of cockroach species were estimated. In this study sticky traps were used to monitor cockroach populations. From a total of 675 residential, official and hospital units inspected, 44.9% were infested with cockroaches. Blattella germanica species was the most abundant i.e 96.7% out of 7251 trapped cockroaches. Laboratory (toxicity) evaluation of hydramethylnon 2% showed 100% mortality against trapped German cockroaches five days after treatment. Four study locations with sizable German cockroach infestation were selected for IPM intervention using Siege® gel bait (hydramethylnon 2%), vacuuming and educational programmes versus control and spray treatments were evaluated. After 15-weeks intervention period, the number of infested units (using cockroach index) improved by 97, 67 and 83% (to achieve clean level of infestation) for IPM intervention units of dormitories, house building and hospital, respectively. The mean percentage reductions of cockroach infestation (based on cockroach trap counts) for IPM intervention were 72, 93 and 88% for dormitories, house building and hospital respectively. The reductions for study locations were significantly higher than pre-treatments and control groups. The IPM intervention method also showed 29% more effective in term of period of effectiveness compared to the spraying method using cypermethrin10% (EC). Additionally, the IPM approach reduced the rate of insecticide application for cockroach control by 9.43 times. However, within the study period the cost for IPM treatment was almost four times higher than the cost for spray treatment. A study on the study locations showed that poor sanitation has a significantly positive impact on intensity of cockroach infestation. The effectiveness of educational programme on sanitation and knowledge of occupants were emphasized in this study. Significant effects of some unsanitary factors such as “dirty and cluttered”, “unwashed dishes left at night” and “leftover foods exposed at places” or “food debris” upon cockroach infestation were highlighted in this study. The results of this study recommended IPM methods as an alternative to manage German cockroach infestation instead of conventional spray method in an urban community